2015
DOI: 10.1111/cas.12585
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, biological and structural properties of romidepsin (FK228) and its analogs as novel HDAC/PI3K dual inhibitors

Abstract: Romidepsin (FK228, depsipeptide) is a potent histone deacetylase (HDAC) inhibitor that has FDA approval for the treatment of cutaneous and peripheral T-cell lymphomas. We have previously reported that FK228 and its analogs have an additional activity as phosphatidylinositol 3-kinase (PI3K) inhibitors, and are defined as HDAC/PI3K dual inhibitors. Because a combination of an HDAC inhibitor and a PI3K inhibitor induces apoptosis in human cancer cells in a synergistic manner, development of an HDAC/PI3K dual inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…CUDC-907 is another dual-acting agent developed by the same research group to inhibit both HDACs and phosphoinositide 3-kinase (PI3K) (Qian et al 2012) and its clinical trials are underway for the treatment of lymphoma and multiple myeloma as well as advanced/relapsed solid tumors. Romidepsin (FK228, depsipeptide) is a potent Class I histone deacetylase inhibitor that has FDA approval for the treatment of cutaneous and peripheral T-cell lymphomas, and recent research demonstrated that FK228 and its analogs (FK-A5 and FK-A11) act as HDACs and PI3K dual inhibitors (Saijo et al 2012; Saijo et al 2015). …”
Section: Anticancer Effect Of Hdac Inhibitorsmentioning
confidence: 99%
“…CUDC-907 is another dual-acting agent developed by the same research group to inhibit both HDACs and phosphoinositide 3-kinase (PI3K) (Qian et al 2012) and its clinical trials are underway for the treatment of lymphoma and multiple myeloma as well as advanced/relapsed solid tumors. Romidepsin (FK228, depsipeptide) is a potent Class I histone deacetylase inhibitor that has FDA approval for the treatment of cutaneous and peripheral T-cell lymphomas, and recent research demonstrated that FK228 and its analogs (FK-A5 and FK-A11) act as HDACs and PI3K dual inhibitors (Saijo et al 2012; Saijo et al 2015). …”
Section: Anticancer Effect Of Hdac Inhibitorsmentioning
confidence: 99%
“…Although HDAC inhibitory activity is equally potent, the PI3K inhibitory activity is different among these analogs. We previously compared their inhibitory activities against HDAC and PI3K and identified FK‐A11 as the most potent HDAC/PI3K dual inhibitor . In the present study, we researched three compounds: FK‐A11, FK228, and FK‐A3.…”
Section: Resultsmentioning
confidence: 95%
“…To evaluate the kinase inhibition profile, we previously reported inhibitory activities of FK‐A11 for 22 kinases . In the present study, inhibitory activities of FK‐A11 were assayed further using a panel including 313 kinases.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…While the total synthesis routes are perhaps not competitive with fermentation for production of the natural products themselves, they are absolutely essential for the synthesis of unnatural analogues. Academic groups such as Ganesan [42] and Williams [43][44][45] as well as others including Luesch [46,47], Jiang [61], de Lera [62], Breit [48] and Katoh [49] have reported the synthesis and HDAC inhibitory activity of analogues. Summarising the data, some general conclusions can be drawn about the SAR of this compound class:…”
Section: Synthetic Analogues Of the Zinc-binding Thiol Natural Productsmentioning
confidence: 99%